Al Qasimi Foundation 2017
DOI: 10.18502/aqf.0042
|View full text |Cite
|
Sign up to set email alerts
|

Curriculum Development in the United Arab Emirates

Abstract: With an increasing emphasis on youth development and employability in the Middle East, the United Arab Emirates (UAE) has made a substantial effort to re- imagine and reform its public education sector. Local education authorities have implemented many reforms to try to shift education from rote memorization toward a skills-based system that prepares students to thrive in the 21st century. This policy paper explores the history of curriculum development in the UAE, the role of various agencies, ministries, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The question that lingers among researches is whether the teachers in government school in the UAE are prepared enough to identify potential leadership traits and potential among elementary schoolchildren, especially at early childhood development level. Another dimension related to this question is whether the government has set enough resources, frameworks, guidelines, and policies that guarantee early childhood leadership preparation (Ridge et al, 2017). That is, whether the government is ensuring that children with potential leadership competencies are identified and nurtured that they can become successful leaders when they advance in education until they graduate after college.…”
Section: Government Involvementmentioning
confidence: 99%
See 3 more Smart Citations
“…The question that lingers among researches is whether the teachers in government school in the UAE are prepared enough to identify potential leadership traits and potential among elementary schoolchildren, especially at early childhood development level. Another dimension related to this question is whether the government has set enough resources, frameworks, guidelines, and policies that guarantee early childhood leadership preparation (Ridge et al, 2017). That is, whether the government is ensuring that children with potential leadership competencies are identified and nurtured that they can become successful leaders when they advance in education until they graduate after college.…”
Section: Government Involvementmentioning
confidence: 99%
“…As explained in literature review that some schools take the initiative in creating their own program internally like public speaking, writing and reading activities, which help to build courage and self confidence in schoolchildren. Meanwhile, at government level, as elaborated by Ridge et al (2017) that MoE and ADEK are playing a critical role in ensuring the education system is supplying the framework and environment for young children' preparation for both career and leadership. As pointed by participant teachers in the findings, this cannot be achieved unless we have benchmarking and rotational teaching among schools or teachers in the same school.…”
Section: Government Involvementmentioning
confidence: 99%
See 2 more Smart Citations
“…A report issued by the Human Development and Knowledge Entity (Salama & Malaa, 2014) found that the total percentage of school achievement in the Arabic subject in most Dubai schools falls below the expected average in total achievement. Although The Ministry of Education of the UEA (2010) has validated the curriculum's appropriateness in terms of the learners' characteristics at each educational stage, many parents and teachers complained about the content's difficulty and its inappropriateness to the students' capabilities (Ridge et al, 2017). In this regard, there is a need for a readability assessment regarding the textbooks in the UAE.…”
Section: Literature Reviewmentioning
confidence: 99%